Induced expression of cytochrome P450 1A and NAD(P)H:quinone oxidoreductase determined at mRNA, protein, and enzyme activity levels in rats exposed to the carcinogenic azo dye 1-phenylazo-2-naphthol (Sudan I) - Stiborová, Marie; Dračínská, Helena; Martínek, Václav; Svášková, Dagmar; Hodek, Petr; Milichovský, Jan; Hejduková, Žaneta; Brotánek, Jaroslav; Schmeiser, Heinz H; Frei, Eva (Chemical research in toxicology, 2013)
Sudan I (1-phenylazo-2-hydroxynaphthol) is a suspected human carcinogen causing tumors in the livers and urinary bladders of rats, mice, and rabbits. Here, we investigated for the first time the influence of Sudan I exposure on the expression of several biotransformation enzymes in the livers, kidneys, and lungs of rats concomitantly at the mRNA and protein levels and assayed their enzymatic activities. We also studied its effect on the formation of Sudan I-derived DNA adducts in vitro. Sudan I increased the total amounts of cytochrome P450 (P450) in all organs tested. Western blots using antibodies raised against various P450s, NADPH:P450 reductase, and NAD(P)H:quinone oxidoreductase 1 (NQO1) showed that the expression of P450 1A1 and NQO1 was induced in the liver, kidney, and lung of rats treated with Sudan I. The higher protein levels correlated with increased enzyme activities of P450 1A1/2 and NQO1. Furthermore, 9.9-, 5.9-, and 2.8-fold increases in the formation of Sudan I oxidative metabolites catalyzed by microsomes isolated from the liver, kidney, and lung, respectively, of rats treated with Sudan I were found. The relative amounts of P450 1A and NQO1 mRNA, measured by real-time polymerase chain reaction (RT-PCR) analysis, demonstrated that Sudan I induced the expression of P450 1A1 and NQO1 mRNA in the liver, kidney, and lung, and of P450 1A2 mRNA in kidney and lung. Finally, microsomes isolated from livers, kidneys, and lungs of Sudan I exposed rats more effectively catalyzed the formation of Sudan I-DNA adducts than microsomes from organs of control rats. This was attributable to the higher P450 1A1 expression. Because P450 1A1 is playing a major role in the bioactivation of Sudan I in rat and human systems, its induction by Sudan I may have a profound effect on cancer risk by this azo dye. In addition, the induction of P450 1A1/2 and NQO1 enzymes can influence individual human susceptibility to other environmental carcinogens and have an effect on cancer risk.
Keywords: Liver; Animals; Kidney; Microsomes; Lung; Rats, Wistar; játra; mikrozomy; Up-Regulation; Coloring Agents; adukty DNA; Naphthols; NAD(P)H Dehydrogenase (Quinone); upregulace; messenger RNA; Carcinogens; Cytochrome P-450 CYP1A1; NAD(P)H dehydrogenasa (chinon); RNA, Messenger; Male; karcinogeny; DNA Adducts; barvicí látky; cytochrom P-450 CYP1A1; krysa rodu Rattus; plíce; cytosol; Cytosol; zvířata; mužské pohlaví; naftoly; ledviny; Rats; potkani Wistar